Dendam Trigantalpati - Hening Sudarsono; Udreka Udreka; Retno Dwi Intarti (Institut Seni Indonesia Yogyakarta, 2021)
AbstractThe puppet performance Dendam Trigantalpati is a reinterpretation of the story of Tri- gantalpati which is sourced to three performance, namely Banjaran Sengkuni Ki Purbo Asmoro, Jumenengan Pandhu Ki Manteb Sudarsono, and Gandamana Tundhung version of Ki Hadi Sugito. The concept of sanggit Soetarno, et al. was used to respond to the three performance. The method used in this work is the exploratory method. The stages that go through are observing the play, selecting and sorting out events, processing events, compiling plays. The result of the reinterpretation of the three performance above is Trigantalpati as someone who cannot control ego and revenge.AbstrakLakon Dendam Trigantalpati adalah sebuah tafsir ulang kisah Trigantalpati yang bersumber pada tiga lakon yaitu lakon Banjaran Sengkuni versi Ki Purbo Asmoro, Jumenengan Pandhu versi Ki Manteb Sudarsono, dan Gandamana Tundhung versi Ki Hadi Sugito. Konsep sanggit Soetarno, dkk. digunakan untuk merespon tiga lakon tersebut. Metode yang digunakan dalam karya ini adalah metode eksploratif. Adapun tahapan yang dilalui adalah mencermati lakon, memilih dan memilah peristiwa, mengolah peristiwa, menyusun lakon. Hasil tafsir ulang dari tiga lakon di atas adalah Trigantalpati sebagai seseorang yang tidak bisa mengendalikan ego dan rasa dendam.